Medicare beneficiaries with more comprehensive primary care physicians report better primary care. (28th December 2022) - O'Malley, Ann S.; Rich, Eugene C.; Ghosh, Arkadipta; Palakal, Maya; Rose, Tyler; Swankoski, Kaylyn; Peikes, Deborah; McCall, Nancy
Abstract: Objective: To examine whether primary care physician (PCP) comprehensiveness is associated with Medicare beneficiaries' overall rating of care from their PCP and staff. Data Sources: We linked Medicare claims with survey data from Medicare beneficiaries attributed to Comprehensive Primary Care Plus (CPC+) physicians and practices. Study Design: We performed regression analyses of the associations between two claims‐based measures of PCP comprehensiveness in 2017 and beneficiaries' rating of care from their PCP and practice staff in 2018. Data Collection/Extraction Methods: The analytic sample included 6228 beneficiaries cared for by 3898 PCPs. Regressions controlled for beneficiary, physician, practice, and market characteristics. Principal Findings: Beneficiaries with more comprehensive PCPs rated care from their PCP and practice staff higher than did those with less comprehensive PCPs. For each comprehensiveness measure, beneficiaries whose PCP was in the 75th percentile were more likely than beneficiaries whose PCP was in the 25th percentile to rate their care highly (2 percentage point difference, p = 0.02). Conclusions: Medicare beneficiaries with more comprehensive PCPs rate overall care from their PCPs and staff higher than those with less comprehensive PCPs.